"A ghost in the system": French nuclear colonialism and the haunting of republicanism. (November 2022) - Caswell, Pierre-Elliot
While France claims to be the nation of universal human rights, its historical intimacy with imperialism would suggest otherwise. The discourse of Republicanism is therefore what allows France to erase and smooth out rhetorical and material incongruities, allowing it to retain its national integrity. This article thus examines the discursive continuities between two constitutive realms of French power: colonialism and nuclearism. I argue that, rather than being separate, these two matrices must be understood as one continuum traversed by the same questions. I analyze their conjoined structure through two historical speeches which both rely on universal Republicanism as justification: Jules Ferry's 1885 intervention at the National Assembly defending his imperial legacy; and Charles de Gaulle's speeches in Papeete, in 1966, promising a radiant future to Tahiti in the postcolonial era. Republican universalism as a discursive tool, however, is not impervious to porousness: it is always haunted by the violence it inflicts and the peoples it affects. An attention to the ghosts that live inside the social fabric produced by this discourse, thus, helps us critically engage Republican universalism and reorganize the hidden, paradoxical aspects of French (post)colonial memory. Haunting, in other words, becomes a decolonial praxis for recovering what has been negated and interrupting the appearance of narrative cohesion that France relies upon.